Post COVID-19 Pandemic Generalized Anxiety Status of Health Professional undergraduate students - Rizwana Kamran, Shazia Tufail, Hina Zafar Raja, Rehan Uddin Alvi, Aqsa Shafique, Muhammad Nasir Saleem, Waqas Sami, Asad Mahmood, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the psychological impact of COVID-19 on mental status of undergraduate medical students, after reopening of educational institutions. Methods: This descriptive, online cross-sectional study was conducted on medical students of Combined Military Hospital Lahore Medical College & Institute of Dentistry, Lahore Pakistan for 6 months from 1st June to 30th November, 2021. Generalized Anxiety Disorder Scale (GAD-7) was used as the study tool. Data was analyzed by using statistical software SPSS - 23. Frequencies and percentages were used for descriptive variables. A univariate analysis was utilized to identify the noticeable associations between traits of sample and the anxiety level in current scenario of COVID-19 pandemic. Finally multivariate logistic regression analyses, odds ratio (OR), and Spearman's correlation coefficient, r, was used to evaluate the association between COVID-19-related stressors and anxiety level. Results: Of the 324 respondents, majority were females residing in urban areas with their parents. Severe anxiety was experienced by 23.8% of students. Female respondents were found to have more anxiety as compared to males (OR = 1.81; 95% CI = 1.173 – 2.815). Moreover, respondents having a relative or an acquaintance infected with COVID-19 reported to have more anxiety (OR = 3.007, 95% CI = 2.377 - 3.804). Conclusion: A significant number of students are experiencing anxiety in the post COVID-19 phase, especially those that had an acquaintance infected with COVID-19. There is a need to look after student's mental health and to implement appropriate psychological strategies and interventions to deal with this level of psychological distress in the students at this phase of pandemic for optimum training of future health professionals. Keywords: Anxiety, COVID-19, healthcare professionals, mental health, medical students, pandemic